Effect of Tibial Component Alignment and Posterior Slope on Tibial Coverage in a Chinese Population: A Three-dimensional Anthropometric Study - Shao, Long; Wang, Ting; Liao, Junyi; Xu, Wei; Liang, Xi; Huang, Wei (The Journal of Knee Surgery, 2020)
The standard for rotational alignment and posterior slope of the tibial component in total knee arthroplasty remains controversial. This study aimed to evaluate the effect of tibial component alignment and posterior slope on tibial coverage. Computer tomographic scans of 101 tibial specimens were used to reconstruct three-dimensional tibia models. A virtual surgery was performed to generate a resection plane with different posterior slopes on the proximal tibia. Symmetrical and anatomical tibial components were placed aligning to the medial one-third of tibial tubercle (Insall) and the medial edge of patella tendon (Akagi), respectively. Differences in coverage and mismatch were evaluated and statistically compared across alignments, slope angles, and genders. The tibial coverage increased from 83.21 to 85.96% for Akagi's alignments and from 85.19 to 87.22% for Insall alignments along with the increasing of posterior slope from 0 to 7 degrees. Regardless of the prosthesis design, there was a significant difference between two rotational alignments as the Insall alignment was significantly higher in tibial coverage. With a slope of 7 degrees, more overhang along with less underhang anteromedially were found in males compared with females. The current anatomical tibial design has a tendency of overhang in the anteromedial zone which does not exist in the symmetrical design. The current tibial baseplate design has better tibial coverage when aligning to the medial third of tibial tuberosity with slopes of 5 and 7 degrees. Gender difference should be taken into account and given priority for prosthesis design.
Keywords: total knee arthroplasty; tibial baseplate; tibial coverage; 3D reconstruction; posterior slope